Analysis of the Influence of Meshing Error and Phase Angle on Load Sharing Characteristic of Compound Planetary Gear Train - Zhou Lu; Wu Shijing; Li Jing; Wang Xiaosun; Zhu Weilin (Jixie chuandong)
Taking the compound planetary gear train as research object,a nonlinear translation- torsion coupled dynamics model is established for compound planetary gear train considering the time- varying meshing stiffness,gear backlash and synthetic meshing errors,and the impact of installation error,eccentric error and the phase angle of them on the load sharing characteristic is analyzed. The results show that the installation errors and eccentric errors of central member will make equal periodic changes for planetary gear,and the installation error of planetary gear will make sustained partial load,while the eccentric error of it makes periodic change for load sharing coefficient. When the installation error phase angle of planetary gear is oriented to the same direction or distributed ons the meshed planetary gear pair,the load sharing coefficient is smaller. The load sharing characteristic is better when eccentric error is distributed on gears with larger difference number of teeth and the error symmetric distribution of planetary gears will gradually reduce the effect of error to load sharing coefficient.